Noncanonical IFN Signaling: Mechanistic Linkage of Genetic and Epigenetic Events - Howard M. Johnson; Chulbul M. Ahmed (Mediators of Inflammation)
The canonical model of cytokine signaling via the JAK/STAT pathway dominates our view of signal transduction but provides no insight into the significance of the simultaneous presence of activated JAKs and STATs in the nucleus of cells treated with cytokines. Such a mechanistic shortcoming challenges the usefulness of the model in its present form. Focusing on the interferon (IFN) cytokines, we have developed a noncanonical model of IFN signaling that naturally connects activated JAKs and STATs at or near response elements of genes that are activated by the IFNs. Specifically, cells treated with IFNγ showed association of activated STAT1α and JAK2 at the GAS element of genes activated by IFNγ. For IFNα treated cells, the association involved activated STAT1α and TYK2 JAK kinase at the ISRE promoter. The power of the noncanonical model is that it provides mechanistic insight into specific gene activation at the level of the associated epigenetics, akin to that of steroid/steroid receptor signaling.